2015
DOI: 10.1007/s10953-015-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

How Can a Free Amino Acid Stabilize a Protein? Insights from Molecular Dynamics Simulation

Abstract: Amino acids such as proline are known as natural osmolytes that can stabilize proteins. But, there is no distinct mechanism at the molecular levels that can explain the stabilization effects of such osmolytes. In this paper, for the first time, the molecular level mechanism of protein stabilization by amino acid proline was studied using molecular dynamics simulation, which led to the following interesting points. Simulations were performed at room and high temperatures using lysozyme as a protein model. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…While DSC results of the thermophysical properties of CPAs in this study showed that isoleucine did not significantly contribute to the ice inhibition effects of the CPA cocktail overall, DE algorithm results showed that post-thaw cell survival could be increased significantly (e.g., from 48.3 to 100%) by 7.5 mM isoleucine. This result is likely a "sweet spot" between the stabilizing (Brennan et al, 2003;Bozorgmehr and Monhemi, 2015) and destabilizing (Taneja and Ahmad, 1994) effects of a hydrophobic amino acid on protein molecules in the cells. While albumin may not have a significant effect on ice formation as shown by DSC, it can act as a scavenger of free radicals alleviating oxidative stress and a carrier of waste produced from any cell damage and stress in freezing and thawing (Boldt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While DSC results of the thermophysical properties of CPAs in this study showed that isoleucine did not significantly contribute to the ice inhibition effects of the CPA cocktail overall, DE algorithm results showed that post-thaw cell survival could be increased significantly (e.g., from 48.3 to 100%) by 7.5 mM isoleucine. This result is likely a "sweet spot" between the stabilizing (Brennan et al, 2003;Bozorgmehr and Monhemi, 2015) and destabilizing (Taneja and Ahmad, 1994) effects of a hydrophobic amino acid on protein molecules in the cells. While albumin may not have a significant effect on ice formation as shown by DSC, it can act as a scavenger of free radicals alleviating oxidative stress and a carrier of waste produced from any cell damage and stress in freezing and thawing (Boldt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…4, the calculated RMSF values for c-AMP residues in simulated systems have been reported. RMSF is a measure of the flexibility of the peptide residues [27][28]. In Fig.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The preferential interaction coefficient of antibodyexcipient mixtures can be measured experimentally via vapor pressure osmometry, 15 and is also accessible via simulation. 11 Numerous experimental [16][17][18][19] and simulation 6,7,[20][21][22][23] studies have been performed on the effects of amino acid and ionic excipients on proteins. However, many of the studies that have been performed focus on how excipients interact with only one or two proteins.…”
Section: Introductionmentioning
confidence: 99%